Comparing skull formation of the Hungarian (Hortobágy) Zackel sheep breed by geometrics morphometrics - Csóri, Zsuzsanna; Gáspárdy, András; Jávor, András (Acta Agraria Debreceniensis, 2015)
This work seeks to explore the morphological changes of the Hungarian (Hortobágy) Zackel sheep's skull, which occurred in the past 50–70 years. In this study, we compared individuals skull forms by geometric morphometric methods. The origin of the breed is not known, we do not know when entering the Carpathian Basin. Therefore, the comparison involved the only known early archaeological findings. We have shown that there is no difference between each period colour variations, but over time change has occurred in the skull formation of the breed.